Rational and Irrational Factors Influencing Bank Stock Prices: GMM Approach - Muhammad Firmansyah; Sri Budi Cantika Yuli; Stanislaw Flejterski (Economics Development Analysis Journal, 2025)
In the dynamic and volatile capital market, understanding the factors that influence stock prices is essential for making informed investment decisions. Stock price movements are influenced by rational, fundamental information, irrational investor behavior, and sentiment. This study aims to analyze the influence of rational and irrational factors on stock prices in the Indonesian banking sector during the 2020-2024 period. The rational variables include price-to-book value (PBV), financial literacy, technology adoption, and interest rates, while irrational influence is represented by investor sentiment or mood. Using a dynamic panel data approach with the Generalized Method of Moments (GMM), this study examines four major Indonesian banks: Bank Mandiri, BNI, BRI, and BCA. The results show that PBV, financial literacy, and technology adoption significantly affect stock prices, while interest rates have a significant negative effect. Additionally, investor sentiment has a considerable positive impact, indicating that emotional and psychological factors can drive stock price movements beyond fundamental valuation. This research presents a novel analytical model that integrates rational and irrational perspectives, offering a comprehensive understanding of stock price volatility in emerging markets. It suggests that investors, companies, and policymakers must consider both fundamental indicators and market sentiment simultaneously to make accurate, timely investment decisions.